Task force on traditional forest knowledge - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Primary aim of the Task Force is to increase understanding of the inter-relationships between traditional and formal (scientific) forest-related knowledge and catalyze potential synergistic application(s) to sustainable forest management. Among its many tasks is to develop and facilitate a protocol for the exchange of information between traditional and western scientific forest knowledge in forest management. It is developing larger regional networks of contributing members representing the forest science community as well as individuals and organizations that represent and/or promote the interests of holders and users of traditional forest-related knowledge.